2020
DOI: 10.1038/s41598-020-68670-3
|View full text |Cite
|
Sign up to set email alerts
|

Low serum lymphocyte level is associated with poor exercise capacity and quality of life in chronic obstructive pulmonary disease

Abstract: The purpose of this study was to evaluate the association of serum lymphocyte level with several clinical parameters in COPD. The study population included 451 COPD patients from the Korean Obstructive Lung Disease cohort study. Serum lymphocyte level was measured every year along with various clinical parameters, such as lung function, 6-min walking (6 MW) distance, quality of life using COPD assessment test (CAT) and St. George's Respiratory Questionnaire (SGRQ) scores, exacerbations, and survival. Serum lym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 37 publications
0
8
2
Order By: Relevance
“…There are studies showing the relationship between low lymphocyte count and poor prognosis in patients with COPD [32] . In addition, the relationship between eosinophils and basophils and COPD has been demonstrated in different studies [33–35] However, in our study, no statistically significant correlation was found between eosinophil values and PNI.…”
Section: Discussioncontrasting
confidence: 67%
“…There are studies showing the relationship between low lymphocyte count and poor prognosis in patients with COPD [32] . In addition, the relationship between eosinophils and basophils and COPD has been demonstrated in different studies [33–35] However, in our study, no statistically significant correlation was found between eosinophil values and PNI.…”
Section: Discussioncontrasting
confidence: 67%
“…A decrease in lymphocyte counts has been described in many respiratory infections caused by viruses [13,14]. Importantly, a low lymphocyte count has been proposed as a worse prognostic marker in patients with influenza virus infection [15,16], chronic obstructive pulmonary disease [17], heart diseases [18,19], and malignancy [20]. In patients infected with SARS-CoV-2, a low lymphocyte count in peripheral blood is a common clinical feature, particularly in patients with severe COVID-19 [2,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Lymphocytopenia has been strongly implicated as a marker of multiple chronic inflammatory pathologies and has been shown as a marker/prognostic indicator of disease severity Studies have reported low lymphocyte count in COPD to be associated with lung function, exercise tolerance, quality of life, disease severity, prognosis, etc. 130 Evidence reports enhanced apoptosis of both CD4 + and CD8 + subtypes, though apoptosis of CD4 + cells seems to predominate in stable COPD. 131 Chronic activation and the resultant enhanced apoptosis could set up an amplified inflammatory cascade triggering progressive lung damage.…”
Section: A) Neutrophils In Copdmentioning
confidence: 99%
“…131,133,134 Multiple mechanisms of lymphocytopenia have been proposed which include chronic activation of lymphocytes and resultant increased lymphocyte apoptosis, stress-induced lymphocytopenia (due to enhanced production of cortisol and pro-inflammatory cytokines), and inflammation-induced tissue trafficking/redistribution of lymphocytes to the site/tissue of damage. 130,135,136 4.B.i) Role of T lymphocytes (Figure 6): 4.B.i.I) CD8+ T lymphocytes: a) Activation of CD8+ T cells (Figure 6): Studies emphasize that COPD is characterized by a chronically activated state of CD8 + T lymphocytes.…”
Section: A) Neutrophils In Copdmentioning
confidence: 99%